2022
DOI: 10.3389/fsurg.2022.901601
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical Study of Percutaneous Epididymal Sperm Aspiration and Testicular Biopsy in the Outcome of ICSI-Assisted Fertility Treatment in Patients with Obstructive Azoospermia

Abstract: ObjectiveTo compare and contrast the effects of percutaneous epididymal sperm aspiration (PESA) and testicular sperm aspiration (TESA) on the outcome of intracytoplasmic sperm injection (ICSI)-assisted fertility treatment in patients with obstructive azoospermia.MethodsPatients with obstructive azoospermia with an age distribution of 20–36 years admitted to the male department of the Reproductive Center of the Second Affiliated Hospital of South China University (Hengyang Nanhua Xing Hui Reproductive Health Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…We have come to the same conclusion since sperm recovered by PESA and TESA had similar clinical pregnancy rates and birth rates, and there was no significant difference compared to the ejaculation group. Another study found that the rate of high-quality blastocysts in the TESA group (82.56%) was significantly higher than that in the PESA group (71.82%), but the embryo implantation rate, pregnancy rate, and miscarriage rate of spermatozoa from the PESA and TESA groups were similar during the ICSI cycle ( 1 ).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We have come to the same conclusion since sperm recovered by PESA and TESA had similar clinical pregnancy rates and birth rates, and there was no significant difference compared to the ejaculation group. Another study found that the rate of high-quality blastocysts in the TESA group (82.56%) was significantly higher than that in the PESA group (71.82%), but the embryo implantation rate, pregnancy rate, and miscarriage rate of spermatozoa from the PESA and TESA groups were similar during the ICSI cycle ( 1 ).…”
Section: Discussionmentioning
confidence: 98%
“…Azoospermia refers to the absence of sperm in semen after three consecutive semen examinations and accounts for 15% of cases of male infertility ( 1 ). Sperm is initially generated in the seminiferous tubules of the testis, collected through these tubules, and temporarily stored in the epididymis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations